Optimizing Colloidal Stability and Transport of Polysaccharide-Coated Magnetic Nanoparticles for Reservoir Management: Effects of Ion Specificity - Shi, Rena; Ow, Hooisweng; Cox, Jason R.; Kmetz, Anthony A.; Chen, Hsieh (Frontiers in Nanotechnology, 2022)
In this work we explore the mechanisms of ion-specific stabilization of a polysaccharide-based coating for colloidal nanomaterials used within the oil & gas industry. While nanotechnology has wide prevalence across multiple industries, its utility within this sector is largely undeveloped but has potential applications in areas including (but not limited to) exploration, drilling and production processes. For example, reservoir contrast agents in the form of superparamagnetic nanoparticles could be used to accurately determine the residual oil saturation distribution in a reservoir and thus advise enhanced oil recovery (EOR) efforts. However, deployment of such materials in oil reservoirs proves challenging in cases where high salinity subsurface environments induce nanoparticle aggregation, leading to loss of mobility. Here, we report the synthesis and characterization of dextran-coated superparamagnetic iron oxide nanoparticles (Dex-SPIONs), the colloidal stability of which was evaluated in various brine formulations at elevated temperatures. Initial dynamic light scattering (DLS) measurements reveal a lack of contingency between particle stability and total electrolyte concentration for samples comprised of synthetic seawater and low-salinity brine, the latter fluid of which possesses higher ionic strength yet preserves colloidal integrity to a much greater extent than its seawater counterpart. Further experiments point to a calcium (Ca2+) ion-specific stabilization effect wherein surface complexation of Ca2+ ions to the dextran periphery improves carbohydrate hydration and thus enhances colloidal stability. Ion selective electrode (ISE) measurements provide additional evidence of the Ca2+ - dextran binding interaction, the role of which also factors significantly into mitigation of polysaccharide degradation (as demonstrated through gel permeation chromatography (GPC)). Finally, we assess the transport of Dex-SPIONs through porous media, including examination of retention properties with respect to variances in ionic composition.